Algorithmic Aspects in Information and Management 4th International Conference, AAIM 2008, Shanghai, China, June 23-25, 2008. Proceedings - Fleischer, Rudolf; Xu, Jinhui; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
This book constitutes the refereed proceedings of the 4th International Conference on Algorithmic Aspects in Information and Management, AAIM 2008, held in Shanghai, China, in June 2008. The 30 revised full papers presented together with abstracts of 2 invited talks were carefully reviewed and selected from 53 submissions. The papers cover original algorithmic research on immediate applications and/or fundamental problems pertinent to information management and management science. Topics addressed are: approximation algorithms, geometric data management, biological data management, graph algorithms, computational finance, mechanism design, computational game theory, network optimization, data structures, operations research, discrete optimization, online algorithms, FPT algorithms, and scheduling algorithms.
Double Partition: (6?+??)-Approximation for Minimum Weight Dominating Set in Unit Disk Graphs -- Nash Bargaining Via Flexible Budget Markets -- On the Minimum Hitting Set of Bundles Problem -- Speed Scaling with a Solar Cell -- Engineering Label-Constrained Shortest-Path Algorithms -- New Upper Bounds on Continuous Tree Edge-Partition Problem -- A Meeting Scheduling Problem Respecting Time and Space -- Fixed-Parameter Algorithms for Kemeny Scores -- The Distributed Wireless Gathering Problem -- Approximating Maximum Edge 2-Coloring in Simple Graphs Via Local Improvement -- An Improved Randomized Approximation Algorithm for Maximum Triangle Packing -- Line Facility Location in Weighted Regions -- Algorithms for Temperature-Aware Task Scheduling in Microprocessor Systems -- Engineering Comparators for Graph Clusterings -- On the Fast Searching Problem -- Confidently Cutting a Cake into Approximately Fair Pieces -- Copeland Voting Fully Resists Constructive Control -- The Complexity of Power-Index Comparison -- Facility Location Problems: A Parameterized View -- Shortest Path Queries in Polygonal Domains -- A Fast 2-Approximation Algorithm for the Minimum Manhattan Network Problem -- Minimum Cost Homomorphism Dichotomy for Oriented Cycles -- Minimum Leaf Out-Branching Problems -- Graphs and Path Equilibria -- No l Grid-Points in Spaces of Small Dimension -- The Secret Santa Problem -- Finding Optimal Refueling Policies in Transportation Networks -- Scale Free Interval Graphs -- On Representation of Planar Graphs by Segments -- An Optimal On-Line Algorithm for Preemptive Scheduling on Two Uniform Machines in the ? p Norm -- An Optimal Strategy for Online Non-uniform Length Order Scheduling -- Large-Scale Parallel Collaborative Filtering for the Netflix Prize.
Keywords: Computer science; Software engineering; Data structures (Computer science).; Algorithms; Numerical analysis; Computer science -- Mathematics; Mathematical statistics; Computer Science; Software Engineering/Programming and Operating Systems; Algorithm Analysis and Problem Complexity; Data Structures; Discrete Mathematics in Computer Science; Numeric Computing; Probability and Statistics in Computer Science; Electronic books